Climate Vulnerability, Communities' Resilience and Child Labour - Delphine Boutin (Institute for the Study of Labor (IZA), 2014)
This article clarifies and quantifies the causal impact of climate change vulnerability on child labour incidence and intensity. For this purpose, we create an index of vulnerability to climate change, composed of biophysical vulnerability and communities' resilience. Both, participation to economic activities and to household chores have been taken into account. We find that climate vulnerability negatively affects child labour incidence and intensity, while has no significant impact on household chores. We conclude that child labour is an adjustment variable to local labour market conditions, not correlated with communities' resilience.
Keywords: J22; J43; O55; Q54; 330; child labour; Malawi; climate change; vulnerability